Biological relationships and frontal sinus similarity in skeletal remains with known genealogical data - Cvrček, Jan; Rmoutilová, Rebeka; Čechová, Markéta; Jor, Tomáš; Velemínská, Jana; Brůžek, Jaroslav; Naňka, Ondřej; Velemínský, Petr (Journal of anatomy, 2020)
Frontal sinus analysis has potential utility for detecting biologically related individuals. However, the methodological approach to its evaluation, as well as its informative value, have been questioned. The aim of this work is to introduce a new approach to evaluating the frontal sinus using the 'external supraorbital line' (ESOL) and to determine whether there are sex differences within families in frontal sinus measurements and whether frontal sinus similarity reflects known genetic relationships in both measurements and morphology. We examined the skeletal remains of 41 adult individuals (25 males, 16 females), all members of one family over four generations (19th to 20th centuries), including individuals with very close consanguinity. CT images of skulls were acquired, and both the dimensions and morphology of the frontal sinuses were analyzed using their portions above the ESOL. No significant sex differences were found within families based on frontal sinus dimensions. Significant relationships were found between biological distance and the maximum height and morphology of the frontal sinuses. The greatest degree of similarity was found among closely related individuals. Additionally, in several cases, there was a greater degree of similarity between first cousins or grandparents and their grandchildren than among siblings or parents and their children. Total surface, volume and width are not significant indicators of relatedness. Known genetic relationships are also supported by individual morphological features. Variability within families with very close consanguineous relationships was lower than within families with common degrees of consanguinity, although differences are significant only for some variables.
Keywords: senioři; Skull; Consanguinity; senioři nad 80 let; pokrevní příbuzenství; Tomography, X-Ray Computed; morphology; frontal sinus anatomy; Middle Aged; mužské pohlaví; tělesné pozůstatky; Adult; mladý dospělý; inbreeding; genealogical documented sample; Aged, 80 and over; lebka; Young Adult; ženské pohlaví; sinus frontalis; Humans; Sex Characteristics; Frontal Sinus; lidé středního věku; dospělí; pohlavní dimorfismus; počítačová rentgenová tomografie; Aged; Body Remains; Female; dimensions; lidé; Male